Isolator-free unidirectional dual-wavelength thulium-doped fiber laser assisted by a two-mode fiber filter. (February 2021) - Qin, Qi; Yan, Fengping; Liu, Yan; Zhang, Luna; Guo, Ying; Han, Wenguo; Bai, Zhuoya; Feng, Ting; Zhou, Hong
Highlights: A wavelength-switchable thulium-doped fiber laser using two-mode fiber filter was proposed. The lasing range of the single-wavelength is ~35.7 nm and the maximum lasing range of the dual-wavelength is ~23.38 nm. The output signal-to-noise-ratio is up to ~60 dB. The wavelength interval of the dual-wavelength can be adjusted from ~4, to 27.36 nm. Abstract: A switchable, thulium-doped, isolator-free fiber laser is proposed and demonstrated. The isolator-free configuration, wavelength selective element and stabilization mechanism were achieved by using a theta cavity design, a two-mode fiber filter and nonlinear polarization rotation, respectively. By properly adjusting the polarization controllers to induce polarization-dependent loss, single- and dual-wavelength outputs can be obtained, and the stability of single- and dual-wavelength operations was measured for 30 min in each case. The single wavelength can be switched from 1959.17 to 1994.86 nm in a lasing range of ~35.7 nm with an optical signal-to-noise ratio (OSNR) of up to ~60 dB. When lasing dual-wavelength, the wavelength interval can be changed from ~4 to 27.36 nm with an OSNR higher than 42 dB, and the maximal lasing range of the dual-wavelength is 23.38 nm. In addition, the wavelength drift and power fluctuation of the proposed fiber laser are less than 0.14 nm and 1.976 dB, respectively, at room temperature, which demonstrates that the thulium-doped fiber laser has favorable wavelength and power stability.